IMPLEMENTASI METODE K-NEAREST NEIGHBORDALAM PERAMALAN PENJUALAN MOBIL BEKAS DI KOTA BATAM - Rafsyanzani s, Firman Firmansyah; Maslan, Andi (Computer Science and Industrial Engineering, 2021)
ABSTRACT The development of information technology begins to enter the most important part in a field of work, information obtained in a job is general and specific. Computers are one of the results of technological developments that can be used to help all types of work, including transactions in business work, with those in the computer software, a user can perform transaction operations quickly. The use of computers is also needed by a marketing. Car sales of PT. Auto Grace is a company engaged in the sale and purchase of used cars, an area domiciled in the city of Batam. Car sales at PT. Auto Grace is currently still unstable and many cars are not sold and are not maintained due to the lack of consumer interest in buying. So that the company does not experience sales problems, the company leadership must be able to find solutions in a way that is able to predict. So this study aims to predict car sales using the K-NN algorithm. The data set used to predict is taken from sales data from 2017 to 2020. After analysis using the K-NN algorithm, with the help of rapidminer software, the accuracy rate in predicting sales is 63.89% with a precision level of 100%. . The question of take that sale car at year 2021 will experience a decline, due to the outbreak of the Covid-19 virus which has resulted in an economic recession.